(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Technology has advanced at a rapid and efficient pace in recent years. Web technology is one of the technologies that allow computers to communicate with one another by using markup languages and multimedia applications. Because it has been noted that many are uninformed of Web technologies, the author has opted to highlight the ideas connected to web technologies in order to address this issue. The author of this review paper discusses Web technologies and their different kinds. Browser is included, as well as a thorough description of its applications. Programming languages, databases, and data formats are also discussed in this article. Motion UI, Serverless architecture, and SPA are just a few of the many trends that will continue in future. Web is adopting new technologies such as Artificial Intelligence (AI), voice search, Blockchain, and the Internet of Things. As indicated by the technologies that power the bespoke web software industry, the future of web technologies is bright.